Quality in health care: its relationship to the work plan methodological - José Emilio Caballero González (Medisur)
The present research deals with the importance of methodological work in teaching and assistance health institutions and the role of the methodological working design as a guiding document to improve the teaching and learning process as well as professional performance. This work shows the results on this aspect obtained through inspections to several health institutions.